Inter- and intra-firm learning synergy through integrating absorptive capacity and employee suggestion processes: The case study of Frauenthal Automotive Toruń company - Andrzej Lis; Agata Sudolska (Journal of Entrepreneurship, Management and Innovation, 2017)

(untitled)
The aim of the paper is to study relationships between the processes of absorptive capacity (inter-firm learning) and learning lessons through employee suggestions (intra-firm learning) and identify potential synergies between them. The research interest is focused on investigating the following problems: (1) How do organizations apply external knowledge to support intra-organizational learning processes? (2) How should the employee suggestion system be organized to increase (or build) absorptive capacity? The exploratory case study analysis is applied to answer research questions and achieve the aim of the study. The unit of analysis is constituted by inter-firm and intra-firm learning processes observed in the firm Frauenthal Automotive Toruń (FTO).